2001
DOI: 10.1007/bf02235480
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions after colorectal surgery cannot be predicted

Abstract: The incidence of unplanned related readmissions 90 days after abdominal or perineal colon resection is 9 percent, and these readmissions could not be predicted from the postoperative course. Because 82 percent of unplanned readmissions occurred within 30 days, this time frame is suitable for computerized comparative analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 9 publications
4
59
3
2
Order By: Relevance
“…In particular, it is necessary to perform periodic follow-up studies in clinics after total gastrectomy in order to assess patients' abdominal symptoms and eating conditions and to intervene in order to prevent malnutrition. A previous report described that 80 % of unexpected readmissions occurred within 30 days, and 50 % of these were within 7 days after discharge in colorectal cancer patients [7,22]. However, regarding specific gastric surgery findings, our study revealed that the incidence of readmissions occurred continuously for up to 6 months postoperatively, because the commonest reasons were malnutrition caused by severe sequelae after gastrectomy.…”
Section: Discussioncontrasting
confidence: 54%
“…In particular, it is necessary to perform periodic follow-up studies in clinics after total gastrectomy in order to assess patients' abdominal symptoms and eating conditions and to intervene in order to prevent malnutrition. A previous report described that 80 % of unexpected readmissions occurred within 30 days, and 50 % of these were within 7 days after discharge in colorectal cancer patients [7,22]. However, regarding specific gastric surgery findings, our study revealed that the incidence of readmissions occurred continuously for up to 6 months postoperatively, because the commonest reasons were malnutrition caused by severe sequelae after gastrectomy.…”
Section: Discussioncontrasting
confidence: 54%
“…The incidence of readmissions within 30 days after colorectal surgery has ranged in the literature from 7 to 10% [34,35]. Although we had high-risk patients in our cohort, the overall 30-day readmission rate was similar to that of previous reports (8.4%), and no significant difference was detected between OC and LC patients.…”
Section: Discussionsupporting
confidence: 86%
“…22 Moreover, POI is one of the most common causes of prolonged hospitalization after abdominal surgery, thus increasing health care resource utilization, and may be a significant causative or contributing factor for hospital readmissions. 5,[23][24][25] Alvimopan is a novel, oral, peripherally acting antagonist of the mu opioid receptor, which is being evaluated in Phase III trials for the management of POI. 26,27 In early studies, alvimopan did not interfere with centrally mediated effects of opioids, such as analgesia and pupillary size.…”
mentioning
confidence: 99%